SPECTRUM OF CLINICAL PRESENTATION AND SURGICAL MANAGEMENT OF INTESTINAL TUBERCULOSIS AT TERTIARY CARE HOSPITAL - Abro, Arshad; Siddiqui, Faisal Ghani; Akhtar, Saleem; Memon, Abdul Sattar (Journal of Ayub Medical College Abbottabad, 2010)
Background: Tuberculosis can involve gastrointestinal tract anywhere from mouth to anus, the peritoneum and pancreatobiliary system. It has varied clinical presentations sometimes mimicking other common abdominal diseases. Tuberculosis continues to be a major problem especially in developing countries, being responsible for 7-10 million new cases and 6 per cent of deaths worldwide annually. Objective was to assess and evaluate various clinical presentations and management of intestinal tuberculosis at Liaquat University Hospital, Jamshoro/Hyderabad. Methods: This 3-year descriptive study was conducted on patients with diagnosed intestinal tuberculosis (by histopathology) in Surgical Unit-I, from January 2006 to December 2008. Detailed history and clinical examination was performed in all the cases. Investigations like Blood CP and ESR, Urea, RBS Electrolytes, Serum A/G Ratio, Ultrasound abdomen, X-Ray chest and abdomen were carried out in all the cases while barium meal, follow through and CT Scan abdomen were performed in selected cases. Preoperative assessment of anatomical site and variety of lesions were also noted. Results: A total of 60 patients with diagnosis of intestinal tuberculosis were admitted and operated. Diagnosis was confirmed by histopathology. Among these, 28 (46.7%) were male, and 32 (54.1%) were female. Variable clinical presentations were seen. Majority of patients (46, 76.7%) had abdominal pain, 26 (43.3%) had vomiting; abdominal distension was seen in 22 (36.7%) cases, diarrhoea and constipation in 16 patients (26.7%) and abdominal mass in 14 patients (23.3%). Majority of patients had ulcerostenotic type of tuberculosis. Single stricture of ileum was seen in 15 (25%) while multiple strictures were seen in 13 (21.7%). Ileal perforation was seen in 6 (10%) patients. Weight loss was seen in 40 (66.7%) patients, fever 36 (60%), night sweats 30 (50%), anorexia in 30 (50%) and pulmonary tuberculosis in 18 (30%) patients. Resection and anastomosis was performed on 24 (40%) cases, right hemicolectomy on 22 (36.7%), stricturoplasty on 8 (13.3%), adhesionolysis on 4 (6.7%), and Ileostomy on 2 (3.3%) patients. Conclusion: Abdominal pain, vomiting, fever and weight loss are the commonest symptoms in abdominal tuberculosis. Single and multiple strictures in the ileum, and mass in the ileocaecal region were the commonest lesions. Definitive surgical procedure like resection and anastomosis, stricturoplasty and right hemicolectomy are the main surgical options. Keywords: Intestinal tuberculosis, tuberculosis, abdominal tuberculosis, TB, stricture, perforation